Genetic risk factors for postoperative atrial fibrillation—a nationwide genome-wide association study (GWAS) - Christensen, Mathias A.; Bonde, Alexander; Sillesen, Martin (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrillation (AF) is a major cause of morbidity with a high prevalence among the elderly and has an established genetic disposition. Surgery is a well-known risk factor for AF; however, it is currently not recognized how much common genetic variants influence the postoperative risk. The purpose of this study was to identify Single Nucleotide Polymorphisms associated with postoperative AF. Methods The UK Biobank was utilized to conduct a Genome-Wide Association Study (GWAS) to identify variants associated with AF after surgery. An initial discovery GWAS was performed in patients that had undergone surgery with subsequent replication in a unique non-surgical cohort. In the surgical cohort, cases were defined as newly diagnosed AF within 30 days after surgery. The threshold for significance was set at 5 x 10-8. Results After quality control, 144,196 surgical patients with 254,068 SNPs were left for analysis. Two variants (rs17042171 (p = 4.86 x 10-15) and rs17042081 (p = 7.12 x 10-15)) near the PITX2-gene reached statistical significance. These variants were replicated in the non-surgical cohort (1.39 x 10-101 and 1.27 x 10-93, respectively). Several other loci were significantly associated with AF in the non-surgical cohort. Conclusion In this GWAS-analysis of a large national biobank, we identified 2 variants that were significantly associated with postoperative AF. These variants were subsequently replicated in a unique non-surgical cohort. These findings bring new insight in the genetics of postoperative AF and may help identify at-risk patients and guide management.